Religion and Education: Law and Practice in the USA - Boris V. NIKOLAEV1; Nataliia A. PAVLOVA1; Mikhail Yu. EMELIN2 (Communications of International Proceedings, 2020)
The article describes topical issues of freedom of religion and prevention of religious discrimination in the US education system. It examines constitutional provisions, judicial decisions, legal materials and the president’s position on the interaction of religion, the state and the education system. The practice of the US Supreme Court on the financing of religious higher education institutions, the conduct of religious ceremonies and the use of religious symbols is analyzed. The article seeks to comment on academic freedom in the context of free expression of religious beliefs, as well as the activities of religious associations in the system of education. The study was funded by the Russian Foundation for Basic Research № 19-011-00559
Keywords: Religion; Education; US Constitutional Law; US Supreme Court; Principle of Equality; Discrimination